(untitled) - Gauwitz, Donna F. (Boston, 2005)
This book provides the fundamentals of drug administration, drug laws, principles of pharmacology, drug handling procedures, physician's orders, routes of administration, dosage calculation, and drug actions related to specific body systems and disorders. New boxed readings for the fifth edition include Legal and Ethical Issues, and Health Care: Today and Tomorrow. Also includes 'CAUTION!' boxes, which provide critical information on common drug administration errors; 'Patient Education' boxes, which teach and reinforce communication skills; critical thinking exercises and Internet activities at the end of each chapter; and step-by-step procedures throughout the text.
Keywords: Drugs,Pharmacology,Dược phẩm,Dược lý học; Administration,Quản lý